Textbook and fairy tale: the pitfalls of didacticism in The Autobiography of Miss Jane Pittman by Ernest J. Gaines (Philologia, 2021)
The Autobiography of Miss Jane Pittman has a clear aim in sight. It is to challenge canonical American history by creating an exemplary “autobiography.” The interviewer- editor’s manipulation of the voice of an illiterate ex-slave is all the more efficacious as it is subtle and paved with good intentions. Such a pedagogical enterprise, however, involves conventional narrative choices which paradoxically end up infantilizing a very old woman and transforming her life story into a latter-day fairy tale.